PP93 Efficacy Of Pharmacological Treatments For Type 2 Diabetes In China. (2019) - Gu, Shuyan; Yu, Hai; Li, Yuanyuan; Shen, Yi; Zhen, Xuemei; Gu, Yuxuan; Wei, Jingming; Shi, Lizheng; Dong, Hengjin
Abstract : Introduction: There are multiple antidiabetic drugs available in China, which vary in their efficacy and safety. However, no study exists that compares all the classes of antidiabetic drugs simultaneously. This study aimed to estimate and compare the efficacy of alternative classes of antidiabetic drugs for Chinese patients with type 2 diabetes, either in a monotherapy regimen or combined with metformin. Methods: A systematic literature review was conducted by searching various literature databases to identify relevant randomized controlled trials published from 1990 to 2016. A meta-analysis was conducted to compare the efficacy of antidiabetic drug monotherapy and placebo or lifestyle interventions (i.e., diet and exercise), and antidiabetic drug plus metformin versus metformin alone, in Chinese patients with type 2 diabetes. An indirect comparison was used to estimate the efficacy of antidiabetic drug plus metformin versus placebo or lifestyle-intervention using metformin as the common comparator. Results: The database search identified 354 relevant studies. Compared with placebo or lifestyle interventions, combination therapies achieved greater reductions in hemoglobin A1c (HbA1c) level (1.9% versus 0.9%), body mass index (BMI) (2.66 versus 0.98 kg/m2), and total cholesterol level (1.07 versus 0.35 mmol/L) than monotherapies. For monotherapies, the top three treatments for reducing HbA1c level were insulin, sulfonylurea, and glucagon-like peptide-1 (GLP-1) receptor agonist. The top three monotherapies for reducing BMI level were metformin, GLP-1 receptor agonist, and α-glycosidase inhibitor. The top three monotherapies for reducing total cholesterol level were metformin, GLP-1 receptor agonist, and dipeptidyl peptidase-4 (DPP-4) inhibitor. For combination therapies, the top three treatments for reducing HbA1c level were GLP-1 receptor agonist plus metformin, insulin plus metformin, and glinide plus metformin. The top three combination therapies for reducing BMI level were glinide plus metformin, GLP-1 receptor agonist plus metformin, and DPP-4 inhibitor plus metformin. The top three combination therapies for reducing total cholesterol level were insulin plus metformin, GLP-1 receptor agonist plus metformin, and α-glycosidase inhibitor plus metformin. Conclusions: Pharmacological treatments had better efficacy than placebo or lifestyle interventions, while combination drug therapies were superior to monotherapies.